Perizinan Berusaha Terintegrasi Secara Elektronik: Suatu Kajian Perspektif Hukum Di Indonesia - Fitri, Winda; Sheerleen, Sheerleen (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Online Single Submission (OSS) or electronically integrated business licensing is a business license issued on behalf of the Ministries and also local governments as regulated and listed in Government Regulation Number 24 of 2018. The establishment of the OSS system provides convenience in accelerating, improving investment and also provides convenience in managing the necessary permits, both individual and non-individual. The purpose of this research is to find out the development of the formation of OSS and also the problems that arise from the implementation of OSS which is regulated in PP No. 24 of 2018. This research was carried out using a normative juridical method by studying and reviewing theories in the literature, namely by studying the legal basis in books. books and regulations related to research. The results of the analysis show that there are various problems from the unpreparedness of the creation of this OSS system, causing various kinds of speculation as well as the pros and cons of the government, which is aimed at accelerating and also increasing investment and business which is packaged in the form of electronic business licenses issued by the Ministry. or Institutions as well as local governments must be further developed, due to various revisions that are deemed necessary to improve the quality of this OSS system so that it can support the main goal of the publication of this OSS system.